The Impact of Arabic Dialects on Enriching the Phenomenon of Metathesis - Nada Sami Nasser (QALAAI ZANIST SCIENTIFIC JOURNAL, 2023)
In my research i studied an important phonemic change for the speaker to reach Ease, easement and lightness which is the metathesis. To search for this phonetic phenomenon in our modern dialects and is there a common factor between what the ancient Arabis dialects came with and what we have achieved today and i strengthened research in the roots of this phenomenon in the dialects of the Arabian Peninsula (semitic dialects) to which i reached important results. Common points between the occurrence of this phenomenon in various dialects which confirms that it is a dialects phonetic phenomenon and the phonetic linguistic change has been closely linked to the dialectical development as it is a phonetic phenomenon as well as being a dialect like many phonetic phenomena.